PENGARUH KETERAMPILAN MENGARSIR TERHADAP HASIL GAMBAR BUNGA MAWAR PADA SISWA KELAS VII SMP SWASTA BUDAYA CIKAMPAK - Vera Vidanti; Mesra Mesra (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to determine whether there is an effect of learning shading techniques on the results of students' pictures of roses, using the quasi-experimental method. The population of this research is the entire class VII students of SMP Swasta Budaya Cikampak which is divided into 3 classes, the sample of this study uses random class selection so that Class VII-1 is selected. Data collection uses practical tests and documentation. Data analysis used descriptive quantitative with t-test statistics. based on the results of the t-test calculation, it is known that there is a significant effect on the results of flower drawings for Class VII students of SMP Budaya Cikampak using shading techniques compared to conventional techniques. This can be seen from the comparison of the average score on the pretest and posttest which increased by 24%.